2017
DOI: 10.20853/31-2-1032
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualisation of an ethical risk assessment for higher education institutions

Abstract: This article examines an ethical risk assessment conducted in one of South African largest higher education institutions, with the purpose to provide a confirmed structure and conceptualisation of ethical risks to be used within the Higher Education sector. A statistical analysis of 1 687 respondents participating in the original ethical risk assessment survey was conducted.Confirmatory factor analyses supported a higher order, multidimensional model of three main factors, namely institutional ethical leadersh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This is consistent with the findings of Gordon et al (2002), who report that general accountability disclosures range between 17.59% and 59.05% with a mean value of 30.54% among 100 US HEIs. The low levels of risk disclosure among HEIs may be due to the fact that the notion of risk management practices is relatively new to HEIs (Grobler, 2017). Further, Panels 2-5 of Table 3 also show that there is wide variability in the distribution of governance quality index, senior management team characteristics, vice-chancellor characteristics and general HEIs characteristic among our sampled HEIs.…”
Section: Descriptive Statistics and Univariate Analysismentioning
confidence: 86%
“…This is consistent with the findings of Gordon et al (2002), who report that general accountability disclosures range between 17.59% and 59.05% with a mean value of 30.54% among 100 US HEIs. The low levels of risk disclosure among HEIs may be due to the fact that the notion of risk management practices is relatively new to HEIs (Grobler, 2017). Further, Panels 2-5 of Table 3 also show that there is wide variability in the distribution of governance quality index, senior management team characteristics, vice-chancellor characteristics and general HEIs characteristic among our sampled HEIs.…”
Section: Descriptive Statistics and Univariate Analysismentioning
confidence: 86%
“…Various authors further outlined that most private companies, when compared with HEIs, have clear objectives, sufficient resources, and effective leaders with effective decisionmaking structures for implementation of business objectives (Mncube 2013;Chetty and Pather 2015). Consequently, risk management content and empirical studies are limited in the higher education sector, especially implementation as the best practices and implementation studies mostly explore the private sector (Brewer and Walker 2010;Moloi 2015a;Grobler and Horne 2017). Moreover, numerous studies confirmed the notion that risk management practices are relatively new in the higher education sector with limited empirical research (Ramirez and Christensen 2013;Grobler and Horne 2017;Andersen 2010;Moloi 2014Moloi , 2016d.…”
Section: Risk Disclosuresmentioning
confidence: 99%
“…Consequently, risk management content and empirical studies are limited in the higher education sector, especially implementation as the best practices and implementation studies mostly explore the private sector (Brewer and Walker 2010;Moloi 2015a;Grobler and Horne 2017). Moreover, numerous studies confirmed the notion that risk management practices are relatively new in the higher education sector with limited empirical research (Ramirez and Christensen 2013;Grobler and Horne 2017;Andersen 2010;Moloi 2014Moloi , 2016d. The slow adoption of risk management by HEIs is largely ascribed to these institutions being known as a place of forming ideas and being resistant to change (Power 2007;Kezar and Meyer 2007).…”
Section: Risk Disclosuresmentioning
confidence: 99%
“…Ultimately, recent research has revealed ethical leadership paradigms (i.e., care, critique, integrity, fairness, and support) are closely associated with educational institutions' well-being and the achievement and satisfaction of educational personnel and students alike (Alonderiene & Majauskaite, 2016;Grobler & Horne, 2017;Güçel et al, 2012;Langlois et al, 2014). In most instances, given the K-12 context, much research identifies ethical leadership as a remarkable facet of high performing schools, particularly ones in poverty-stricken areas (Fullan, 2003;Shapiro & Stefkovich, 2011).…”
Section: Introductionmentioning
confidence: 99%